Clinico-hematological profile and coronary artery changes detected at initial echocardiography in children with Kawasaki disease: a 12 years single centered experience from a tertiary care referral center of Bangladesh - Ali, M. Asif; Haque, Mujammel; Islam, M. Ridwanul; Talukder, Manik K. (International Journal of Contemporary Pediatrics, 2025)
Background: Kawasaki disease (KD) is the most common cause of acquired heart disease in childhood. Coronary artery abnormalities may occur in 15-25% of children with KD. Our study aimed to analyze the demographic, clinical, laboratory profile and initial echocardiographic changes of coronary arteries among KD patients admitted in a tertiary care center in Bangladesh. Methods: This was a retrospective study of 66 children diagnosed with KD admitted in the Department of Paediatrics from July 2010 to March 2023 at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Results: We found that 51.5% patients had complete KD while 48.5% had incomplete KD. Clinical profile showed fever, extremity changes, oral mucosal changes, maculopapular rash, cervical lymphadenopathy and non-purulent conjunctivitis in 100%, 72.7%, 68.2%, 62.1%, 50% and 48.5% cases respectively. Echocardiography done at the time of diagnosis demonstrated coronary artery abnormalities among 48.5% cases. Overall, 15.2% cases had small aneurysms, 7.6% patients had medium aneurysms and 4.5% cases had large or giant aneurysms in our study. Majority of the patients had developed LCA abnormalities (42.4%) followed by RCA abnormalities in 21.2% cases and LCX abnormalities in 7.6% cases. Conclusions: In this study, we observed a slightly higher frequency of the complete KD (51.5%) in comparison to incomplete KD patients. Fever was the most consistent clinical feature followed by extremity changes, oral mucosal changes, maculopapular rash, cervical lymphadenopathy and lastly non-purulent conjunctivitis. Initial echocardiography revealed 48.5% patients with KD had coronary artery abnormalities with a predilection towards left coronary artery.